Allelic variations in putative antimalarial drug resistance and vaccine candidate genes among Plasmodium vivax reference genomes - Tamang, Suman; Arya, Aditi; Singh, Vineeta (Frontiers in Malaria, 2025)
ObjectivesPlasmodium vivax is the most widespread Plasmodium spp. globally and the second most common cause of human malaria. However, very little is known about its biology due to the lack of continuous in vitro/ex vivo culture. In such circumstances, genomic studies provide an alternative for understanding the biology of P. vivax parasites. To date, most of the genomic studies on P. vivax have been based on Sal-I as a reference genome; however, with the recent release of the PvP01 and PvW1 reference genomes with higher quality and improved assemblies following continual improvements in annotation, the adoption of these genomes as a reference for genomic studies appears more advantageous. In this study, allelic differences in putative antimalarial drug resistance genes and vaccine candidate genes with assembly features of these three genomes are analyzed and summarized.MethodsThe nucleotide and amino acid sequences of five P. vivax putative antimalarial drug resistance genes and three vaccine candidate genes for all three reference genomes (i.e., Sal-I, PvP01, and PvW1) were retrieved from PlasmoDB and aligned together using MEGA11. Any differences in the nucleotide and codon sequences between the genomes were recorded.ResultsVarious allelic differences in the putative antimalarial drug resistance and vaccine candidate genes between the three reference genomes were observed, which included the positions previously identified as candidate markers for these gene variants.ConclusionsAs antimalarial drug resistance genotyping studies rely on candidate genetic markers to classify resistant or sensitive parasites, knowledge of the allelic differences among references is important. Furthermore, the heterogeneity of the vaccine candidate genes should be taken into account when designing vaccines for P. vivax.